The Church and National Development in Nigeria: A Historical Survey - Oluwasegun Aluko; Caleb Adeleye; Olusegun Olakanmi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
This historical survey looks at the many-sided roles of the church in national development in Nigeria, ranging from education and health to politics and social services. The influence of the Church, tracing from the colonial era when missionary activities originally provided the foundation for Western-type education and health infrastructures to the post-colonial period when it played a key role in shaping national leaders and encouraging moral governance, is traced. The methodology employs a qualitative historical analysis, utilising primary and secondary sources such as missionary records, archival documents, and academic literature. Through institutions like the Christian Association of Nigeria (CAN), the church speaks out for political justice, peace, and national cohesion. It has equally been at the forefront of alleviating poverty and social inequality, contributing to nation-building through its charitable initiatives and the establishment of hospitals and schools. The challenges of modern times range from the commercialisation of religion to tensions between different religious groups, which most often make it quite hard for the church to effectively take on its role in fostering national unity. It is still growing in its role, with an ever-increasing incorporation of SDGs in the church's ministries contributing to social justice, gender equality, and sustainable development. The survey has, therefore, emphasised the continued relevance of the church's role in resolving biting social problems in Nigeria and offers reflections on its prospects for national development.